Analisis Hasil Pengukuran Performansi Jaringan 4G LTE 1800 MHz di Area Sokaraja Tengah Kota Purwokerto Menggunakan Genex Asistant Versi 3.18 - Ferdinanta Karo Karo; Eka Setia Nugraha; Fikri Nizar Gustiyana (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2019)
The implementation of 4G LTE network and its advantages gave us faster speed of mobile network. We need to know the performance of LTE mobile network in Sokaraja Tengah – Indonesia, which deployed by Telkomsel network provider by comparing its RSRP, SINR, RSRQ, and throughput using drive test method of Genex Probe. Signal performance was measured by drive test dedicated mode on the streamed videos and analyzed with Genex Assistant. The result shows that generally Telkomsel’s 4G LTE network in Sokaraja Tengah has 99.7% of (-70) – (-90) dBm RSRP value, 85.09% of 1-15 SINR value, 99.23% of (-15)-0 dBm RSRQ value, average uplink 2575 kbps and downlink 1530 kbps of throughput.